HYPNOSOSMN.MP3: ALAT HIPNOSIS UNTUK MEMBANTU ORANG-ORANG DENGAN KESULITAN TIDUR - Suharya, Fitra; Varesty, Vonnie; Agia, Muhamad Irfan; Aprilia, Gerizcha (Program Kreativitas Mahasiswa - Karsa Cipta, 2013)
Sleep is a natural process for releasing physical fatigue and mental fatigue. Sleep difficulty is a condition where a person has difficulty in penetrating sleep phase so she stays awake when she wants to sleep. Individual with sleep difficulty can overcome her problem by consuming sleeping pills, relaxation massage, or the services of a professional hypnotherapist. Although effective, sleeping pills can cause negative impact in the long-term. Likewise with reflexology, though not causing side effects, it is less effective and less flexible. One of the new way is to use the proposed new "Hypnosomn.mp3".Hypnosomn.mp3 is a hypnosis tool with a core file which is formatted in digital data form. Mp3. The core file consists of hypnosis scripts, sounds of nature, and the scripts suggestion sleep. Core files are then inserted into complementary media tools into one package hypnosis. Hypnosomn.mp3 is an alternative solution for sleep problems, ready to use, easy to carry, and can be used anytime and anywhere.